Transperineal prostate biopsy identifies locations of clinically significant prostate cancer in men considering focal therapy with PI‐RADS 3–5 regions of interest. Issue 6 (5th October 2021) - Stone, Nelson; Skouteris, Vassilios; Chang, Samuel; Klimis, Athanasios; Lucia, M. Scott
Abstract: Objectives: To determine the benefit of performing transperineal prostate mapping biopsy (TPMB) following multiparametric magnetic resonance imaging (mpMRI) to increase the identification of clinically significant prostate cancer (csPCa) with Gleason grade group (GG) ≥ 2 and their locations outside of the PI‐RADS v2 3–5 category lesions. Methods: mpMRI was performed in 80 men prior TPMB from two institutions. The mpMRI was considered clinically significant (csMRI) if it contained one or more PI‐RADS 3–5 category lesion. mpMRI findings were compared against csPCa diagnosed by TPMB, performed between 16 November 2010, and 13 September 2019, for the entire gland, both lobes and to the right and left anterior and right and left posterior quadrants (RA, LA, RP and LP). Sensitivity, specificity, positive and negative predictive values (PPV, NPV), accuracy and the area under curve (AUC) were determined. Thirteen men also underwent radical prostatectomy and had comparison of TPMB pathology to prostatectomy specimen grading. Results: TPMB was positive in 60/80 (75%) of which 32 (53.3%) were csPCa. csPCa was present in the RA in 9 (11.3%), LA in 11 (13.8%), RP in 25 (31.3%) and LP in 27 (33.8%) and involved 1 quadrant in 7 (21.9%), 2 quadrants in 12 (37.5%), 3 quadrants in 11 (34.4%) and all 4 quadrants in 2 (6.3%) patients; 57/80 (71.3%) men had a mpMRIs with lesions designated as PI‐RADS 3 in 24 (30%), 4 in 25 (31.3%) and 5 in 8 (10%). A csMRI was present in the RA in 7 (8.8%), LA in 8 (10%), RP in 31 (38.8%) and in the LP in 29 (36.3%), which were limited to one quadrant in 39 (68.4%), 2 quadrants in 16 (28.1%), and 3 quadrants in 2 (3.5%). Sensitivity, specificity, PPV, and NPV were determined from the results of the TPMB and were for the entire gland 81.3%, 35.4%, 45.6% and 73.9%. There were 31 csMRIs involving the right posterior of the gland but only 25 csPCa by TPMB of which 12/31 (38.7%) were concordant for high grade disease. There were 29 men who have a csMRI in the left posterior quadrant, and 14 (48.3%) were concordant with csPCa from the TPMB. Conclusions: MpMRI should be supplemented with TPMB to correctly identify the regions of the prostate that would require ablation in men considering focal therapy.